Medicolegal applications of PET scans. - Mehr SH; Gerdes SL (NeuroRehabilitation, 2001)
Courts will allow doctors to testify about the results of PET scans only if doctors provide proper legal foundation for their opinions. Doctors must document that they have used proper scientific techniques in performing the scan. They must also be prepared to explain why PET scans are scientifically reliable when used on patients with mild traumatic brain injury (TBI).